S2k guidelines for Merkel cell carcinoma (MCC, neuroendocrine carcinoma of the skin) – update 2018. (6th May 2019) - Becker, Jürgen C.; Eigentler, Thomas; Frerich, Bernhard; Gambichler, Thilo; Grabbe, Stephan; Höller, Ulrike; Klumpp, Bernhard; Loquai, Carmen; Krause‐Bergmann, Albrecht; Müller‐Richter, Urs; Pföhler, Claudia; Schneider‐Burrus, Sylke; et al.
Summary: Merkel cell carcinoma (MCC, ICD‐O M8247 / 3) is a rare malignant primary skin tumor with epithelial and neuroendocrine differentiation. The neoplastic cells share many morphological, immunohistochemical and ultrastructural characteristics with Merkel cells of the skin. The diagnosis of MCC is rarely made on clinical grounds. Histological and immunohistochemical studies are usually required to confirm the clinical suspicion. Given the frequent occurrence of occult lymph node metastasis, sentinel lymph node biopsy should be performed once distant metastasis has been ruled out by cross‐sectional imaging. Primary tumors without evidence of organ metastases are treated with complete surgical excision with appropriate surgical margins. Radiation therapy should be considered at all stages of the disease. For advanced MCC that is no longer amenable to curative treatment by surgery or radiation therapy, there is currently no established systemic therapy for which an improvement in recurrence‐free survival or overall survival has been demonstrated in a prospective randomized trial. However, immunotherapy using PD‐1/PD‐L1 blockade seems to be superior to chemotherapy. Various factors warrant that further diagnostic and therapeutic interventions be determined by an interdisciplinary tumor board. These factors include the tumor's aggressiveness, the frequent indication for sentinel lymph node biopsy along with the frequent occurrence in the head and neck region, the potential indication for adjuvant radiation therapy as well as the complexity of the required diagnostic workup.